Negative E-WOM “Perang Indomie dan Mie Gaga” dalam mempengaruhi Switching Intention dengan Brand Trust sebagai mediasi - Alex Sander, Ongky; Muzammil, Oktafalia Marisa; Putri, Yohanna (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
In mid-2023, viral news on various social media such as Tiktok, Instagram and Youtube regarding the case of two well-known instant noodle brands in Indonesia, namely Indomie and Mie Gaga. This became negative news for the Indomie brand because of the issue that the owner of Indomie, Sudono Salim, “betrayed” his business partner, Djajadi Djaja, who is currently the owner of the Mie Gaga brand. The negative news (negative ewom) that went viral on social media resulted in various negative responses from the public, especially the decline in brand trust in the Indomie brand. As a result of the negative issues circulating, a group of consumers began to switch (switching intention) from Indomie products to Mie Gaga products. Based on the phenomenon between Indomie and Mie Gaga, it can be seen that negative e-wom can influence consumers to switch to other brand products, because negative e-wom can reduce consumer trust. This research uses Structure Equation Modeling (SEM) involving 217 Indomie consumers who have known the news of Indomie and Mie Gaga. In explaining the results of the research objectives to be achieved, a survey method was used by distributing questionnaires with Likert measurement scale (1-5) and measuring instruments, namely SMART-PLS 3. The results showed that Negative E-WOM and Brand trust have a significant effect on consumer Switching intention. Meanwhile, Negative E-WOM has no significant effect on Brand trust. Finally, Brand trust is not a moderator variable that can predict the effect of Negative E-WOM on Switching intention